Hantzsch-Like One-Pot Three-Component Synthesis of Heptaazadicyclopenta[a,j]anthracenes: A New Ring System - Abdelmoniem, Amr M.; Sroor, Farid M.; Ramadan, Muhammed A.; Ghozlan, Said A. S.; Abdelhamid, Ismail A. (Synlett, 2020)
A concise and efficient approach to novel tetrahydroheptaazadicyclopenta[a,j]anthracene-5,7-diones, by the reaction of aldehydes with two moles of 7-amino-2-methyl-3-phenylpyrazolo[1,5-a]pyrimidin-5-one is reported. Also, pyrazolo[1,5-a]pyrido[3,2-e]pyrimidine-7-carbonitrile derivatives were prepared by a three-component reaction of aldehydes, 7-amino-2-methyl-3-phenylpyrazolo[1,5-a]pyrimidin-5-one, and 3-aminocrotononitrile.
Keywords: pyrazolopyrimidinones; Hantzsch reaction; heptaazadicyclopentaanthracenes; pyrazolopyridopyrimidines; multicomponent reaction